2019
DOI: 10.1097/mao.0000000000002106
|View full text |Cite
|
Sign up to set email alerts
|

Steroids for Acute Vestibular Neuronitis—the Earlier the Treatment, the Better the Outcome?

Abstract: Objective: To present findings that suggest steroid treatment within 24 hours of onset of vestibular neuronitis results in better restitution of vestibular function than treatment between 25 and 72 hours. Patients: Thirty-three consecutive patients (17 men, 16 women, mean age 57 yr, range 17–85 yr) with acute vestibular neuronitis and treated with steroids within 72 hours after symptom onset. Patients were divided into two groups depending on if they were treated within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 20 publications
2
50
0
3
Order By: Relevance
“…On the contrary, a retrospective study demonstrated that patients receiving a steroid treatment (methylprednisolone 1 mg/kg for 5 days with an additional 5 days of 0.5 mg/ kg) showed better results in terms of vestibular recovery and symptomatic relief/improvement compared to patients receiving non-glucocorticoid treatment [39]. Besides these controversial results, it has been suggested that steroid treatment started within 24 h of onset of AUV results in better recovery of vestibular function than treatment between 25 and 72 h [40]. Especially in older patients, this therapeutic option should be evaluated carefully due to the risk of possible adverse effects of steroids such as infections, blood clots, fractures, hyperglycemia, and hypertension.…”
Section: Acute Unilateral Vestibulopathy (Auv)mentioning
confidence: 99%
“…On the contrary, a retrospective study demonstrated that patients receiving a steroid treatment (methylprednisolone 1 mg/kg for 5 days with an additional 5 days of 0.5 mg/ kg) showed better results in terms of vestibular recovery and symptomatic relief/improvement compared to patients receiving non-glucocorticoid treatment [39]. Besides these controversial results, it has been suggested that steroid treatment started within 24 h of onset of AUV results in better recovery of vestibular function than treatment between 25 and 72 h [40]. Especially in older patients, this therapeutic option should be evaluated carefully due to the risk of possible adverse effects of steroids such as infections, blood clots, fractures, hyperglycemia, and hypertension.…”
Section: Acute Unilateral Vestibulopathy (Auv)mentioning
confidence: 99%
“…The effect of these hormones on bone metabolism is negative ( Mitra, 2011 ), as shown by the appearance of osteoporosis in subjects chronically treated with these steroids. However, intratympanic or systemic administration of corticosteroids is a standard treatment to control the symptoms of several vertiginous syndromes, such as Meniere’s disease or vestibular neuritis ( Patel, 2017 ; Sjögren et al., 2019 ). It is because these hormones are anti-inflammatory and play a role in fluid and electrolyte regulation, therefore, improving homeostasis of the inner ear.…”
Section: Otoconial Mineralization and Bppvmentioning
confidence: 99%
“…5 After that review, several reports issued newly an interest in the use of corticosteroids for VN. 6,7 Ismail et al 6 proposed that corticosteroids may accelerate the recovery of VN. Sjogren et al 7 describe a critical period when treatment with corticosteroids could be effective.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Ismail et al 6 proposed that corticosteroids may accelerate the recovery of VN. Sjogren et al 7 describe a critical period when treatment with corticosteroids could be effective. In addition, the Cochrane review published in 2011 proposed the need for future studies, including those addressing health-related quality of life, subjective measures, and objective measures.…”
Section: Introductionmentioning
confidence: 99%